Factors Affecting Supply Chain Management: Trust, Collaborative Communication, and Information Sharing - Afif Maulana Ibrahim; Hapzi Ali (Dinasti Publisher, 2024)
This research investigates critical factors influencing supply chain management, with a specific focus on trust, collaborative communication, and information sharing. This research used literature review which is drawing insights from a comprehensive review of recent literature, this study examines the findings of various authors to identify commonalities, differences, and gaps in the existing knowledge base. The results of this research are (1) Trust affects Supply Chain Management; (2) Collaborative Communication affects Supply Chain Management; (3) Information Sharing affects Supply Chain Management.